Haemophilus influenzae type b conjugate vaccine trial in Oxford: implications for the United Kingdom. Issue 4 (April 1989) - Tudor-Williams, G; Frankland, J; Isaacs, D; Mayon-White, R T; MacFarlane, J A; Rees, D G; Moxon, E R
Abstract : The safety and immunogenicity of a Haemophilus influenzae type b conjugate vaccine was investigated in 103 infants immunised at 3, 5, and 9 months of age; the infants also received diphtheria, pertussis, and tetanus and polio vaccines. Side effects were compared with 99 matched infants receiving diphtheria, pertussis, and tetanus and polio vaccines only. No serious side effects were observed and the incidence of minor side effects was no greater in the recipients of H influenzae type b conjugate vaccine. Two doses of the vaccine (standard and low) were compared: geometric mean titres of serum anticapsular antibody rose from 0.11 microgram/ml before immunisation to 26.4 micrograms/ml after three immunisations with the standard dose and 14.6 micrograms/ml with the low dose. The geometric mean titre among 21 unimmunized infants at this age was 0.06 micrograms/ml. Both doses therefore generated antibody concentrations likely to be protective after three immunisations. There were no non-responders. Incorporation of an H influenzae type b conjugate vaccine into the primary immunisation schedule has the potential for preventing over 1000 cases of systemic H influenzae type b disease and 50 deaths each year in the United Kingdom.